Development of E-Catalog Design as a Promotional Medium to Support Digital Transformation and Professional Certification for Batik Communities - Amalia, Amalia; Paramita, Cinantya; Izzhati, Dwi Nurul; Tjahyono, Rudi; Syamwil, Rodia; Febrian, Nanda Dwi; Nugroho, Adi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
The Indonesian government is encouraging the digitalization of public procurement to strengthen the use of domestic products and services, including competency certification. The LSP Batik is a professional certification institution that assesses the competencies of batik artisans and communities. They face challenges due to limited digitalization and restricted access to certification information. This project aims to develop an e-catalog design for the certification schemes and to enhance the understanding of digital procurement. A Participatory Design approach was adopted, actively engaging both end-users and key stakeholders across all phases of the co-creation and evaluation process. The project culminated in the development of an e-catalog integrated with the government's e-procurement portal, designed to modernize the services of LSP Batik. The design evaluation yielded high suitability scores for illustration and contrast (100%), followed by the completeness of information (88%), and branding and clarity of information (75%). Furthermore, user assessment indicated a high degree of comprehension in product search functionality (100%), while understanding of product comparison (63%) and showcase development (50%) was moderate, suggesting areas for future improvement.